A study on obstetric care in a primary health center of South Assam district, India - Dey, Ajit Kumar; Chutia, Debojit (International Journal Of Community Medicine And Public Health, 2018)
Background: Maternal and child health are critically important in a country that is experiencing high infant mortality and maternal mortality. Research all over the world has suggested that one of the major solutions to this problem is availability of Emergency Obstetric Care services within the reach of people. Objectives of the study were to examine profile of mothers who have delivered in health facility during a year and the interplay of various factors in child birth and newborn outcome. Methods: Retrospective cross sectional study conducted by collecting information in predesigned format from medical records. Appropriate statistical methods and test of significance performed for qualitative and quantitative variables. Results: Out of 539 women, the majority of 42.9% were in the age group 20-25 years, the mean age (SD) of mother was 24.1 years (±4.09). Out of total 539 vaginal deliveries, 56.6% cases episiotomy was performed. 41.6% deliveries occurred from 8 AM to 4 PM. The mean birth weight was 2.830 kg SD 0.439 and low birth prevalence 16.0%. Parity with time to delivery after admission in different age groups revealed significant association (X2=66.456, p=0.000). Women aged less than 20 years are 12 times more at risk of episiotomy performed. The multivariate logistic regression analysis shows 60.67% specificity and 85.59% sensitivity in predicting episiotomy. Conclusions: From study it is evident that women report to hospital late in labor hence there is urgent need to provide quality antenatal care services at village and PHC level and augment awareness among the community for promotion of safe motherhood.